2001
DOI: 10.1007/s004380000409
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Saccharomyces cerevisiae stress resistance, through the overactivation of the heat shock response resulting from defects in the Hsp90 chaperone, does not extend replicative life span but can be associated with slower chronological ageing of nondividing cells

Abstract: Recent studies on Drosophila and Caenorhabditis elegans indicate that increases in stress resistance result in a longer chronological life span, an effect that must operate primarily on the postmitotic tissues of the adult. Stress resistance can be increased through decreases in Hsp90 chaperone activity, since Hsp90 acts to downregulate the activity of heat shock transcription factor. This study investigated whether the increases in stress resistance associated with reduced Hsp90 chaperone activity influence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 34 publications
(55 reference statements)
1
14
0
Order By: Relevance
“…We confirmed that yHsp90-T22I displayed a higher basal and heat-induced (39°C for 40 min) Hsf1 activity compared to WT cells [39] (Figure 3B), while Hsf1 activity was significantly diminished in the phospho-mimetic yHsp90-T22E mutant. At the same time, Hsf1 activity in yHsp90-T22A mutant yeast was equivalent to that of yeast expressing WT yHsp90.…”
Section: Ck2 Phosphorylation Of Threonine 22 Impacts Chaperoning Of Hsupporting
confidence: 67%
“…We confirmed that yHsp90-T22I displayed a higher basal and heat-induced (39°C for 40 min) Hsf1 activity compared to WT cells [39] (Figure 3B), while Hsf1 activity was significantly diminished in the phospho-mimetic yHsp90-T22E mutant. At the same time, Hsf1 activity in yHsp90-T22A mutant yeast was equivalent to that of yeast expressing WT yHsp90.…”
Section: Ck2 Phosphorylation Of Threonine 22 Impacts Chaperoning Of Hsupporting
confidence: 67%
“…Studies in metazoan systems demonstrated association between Hsps, most notably Hsp90, and HSF1 both in vivo and in vitro (8 -10). A regulatory chaperone-Hsf1 interaction in yeast was long supported by genetic studies in which the loss of constitutive Hsp70 or loss of a functional Hsp90 led to derepression of Hsf1 activity (11)(12)(13). Additionally, the constitutively expressed Hsp70 Ssa1 was found to utilize two surfaceexposed cysteine residues to regulate Hsf1 as a sensor for thiolreactive stress (14).…”
Section: Protein Homeostasis and Cellular Fitness In The Presence Of mentioning
confidence: 99%
“…Hsp90 is a negative regulator of heat shock transcription factor 1 (HSF1), such that its inhibition leads to the formation of the active HSF-1 homotrimers needed for the induction of the heat shock response [44,45]. At least in the yeast model system, a point mutation in Hsp90 is capable of rendering HSF-1 constitutively active [46]. …”
Section: Resistance Caused By N-domain Inhibitors Activating the Heatmentioning
confidence: 99%